Divergent Synthesis of Organophosphate [(11)C]VX- and [(11)C]Sarin-Surrogates from a Common Set of Starting Materials - Hayes, Thomas R. (Appl Radiat Isot, 2019)
Radiolabeled 1-[(11)C]ethyl, 4-nitrophenyl methylphosphonate (VX-surrogate) and 2-[(11)C]-propanyl, 4-nitrophenyl methylphosphonate (sarin surrogate) were developed as organophosphate (OP) tracers. The [(11)C]ethyl- and [(11)C]isopropyl-iodide radiolabeled synthons were obtained by temperature controlled, in loop reactions of [(11) C]CO(2) with MeMgBr followed by reduction with LiAlH(4), then reaction with HI. Distillation of the [(11)C]alkyl iodides into a solution of hydrogen (4-nitrophenyl)methylphosphonate and cesium carbonate afforded the desired tracers in > 95% radiochemical purity, yields from [(11)C]CO(2) of 1-3% and 1.7-15.1 GBq/mmol molar activities.